Roles of plant hormones and anti-apoptosis genes during drought stress in rice (Oryza sativa L.) - Ubaidillah, Mohammad (3 Biotech, 2016)
We previously identified the rice (Oryza sativa) senescence-associated gene OsSAP which encodes a highly conserved protein involved in anti-apoptotic activity. This novel Bax suppressor-related gene regulates tolerance to multiple stresses in yeast. Here, we show the effects of drought stress on leaf and root tissues of plants over-expressing OsSAP in relation to the levels of phytohormones, abscisic acid (ABA), jasmonic acid (JA), indole-3-carboxylic acid (ICA), gibberellic acid (GA(3)), and zeatin. Results showed that rice plants over-expressing SAP were tolerant to drought stress compared to wild type and the plants over-expressing AtBI-1, which is a homolog of the human Bax inhibitor-1 in Arabidopsis. ABA and JA levels in OsSAP and AtBI-1 transgenic plants consistently increased up to at least 3 days after drought treatment, whereas lower GA(3) levels were recorded during early drought period. Comparison between control and transgenic plants overexpressing anti-apoptosis genes OsSAP and AtBI-1 resulted in different patterns of hormone levels, indicating that these genes are involved in the plant responses to drought stress and present an opportunity for further study on drought stress tolerance in rice and other plant species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13205-016-0564-x) contains supplementary material, which is available to authorized users.